(untitled) (Journal of Computational Mathematics, 2001)
Estimations of lower bounds for the fundamental functions of (0,1,2,3) interpolation are given. Based on this result conditions for convergence of (0,1,2,3) interpolation and for Grünwald-type thoerem are essentially simplified and improved.